Comparison of Students' Ability to Work Inventory Questions at SMK Negeri 1 Pulutan (Economic Education Analysis Journal, 2022)
This study aimed to determine whether there is a comparison of students' abilities in working on inventory questions at SMK Negeri 1 Pemulutan. The subjects in this study were students of class XII Accounting at SMK Negeri 1 Pemulutan, from 98 students 66 students were taken to be used as research samples. Data collection techniques were documentation and tests, with the instrument in the form of test questions—the data analysis technique used one-way ANOVA (one-way ANOVA or F test) using SPSS version 22. From the results of the analysis using the F test with SPSS version 22, the F-count was 4.086, and the F-table of 3.15 with a dk of 66 and a significance level of 5%. Because F-count was greater than F-table (4.086 > 3.15), Ho was rejected and Ha was accepted. The average student test results in solving inventory questions using the FIFO method was 85.27, LIFO was 81.10, and AVERAGE was 74.65. This showed that there was a comparison of students' abilities in working on inventory questions at SMK Negeri 1 Pemulutan, as well as in the process of working on the easy method, namely the FIFO method, and the difficult method, the Average method.